Refrigeration, home and commercial - Anderson, Edwin P. 1895- (Macmillan, 1990)
Refrigeration: Home and Commercial is a standard reference for the installation, operation, and servicing of refrigeration equipment. Topics covered include the fundamentals of refrigeration, refrigerants, compressors, installation methods, thermoelectric cooling, and absorption systems, and there is a special emphasis on electrical circuitry. Refrigeration also discusses locker plants, brine systems, and ice-making systems, cold storage, fans, blowers, piping, and pumps. Load calculations are explained and reviewed. Refrigeration has been completely revised and updated and deals with both new and older equipment. Written in clear, easy-to-understand language, it contains troubleshooting charts to assist in the diagnosis and solution of problems, and numerous illustrations for easy visualization of all topics covered.